The Influence of Training and Career Development on Employee Retention Mediated by Job Satisfaction - Nasution, anisyah Risky; Suhairi, Suhairi; Nurbaiti, Nurbaiti (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
PT. Pegadaian Kanwil I Medan acknowledges the importance of investing in employee development. However, despite these efforts, the company faces challenges with low employee retention rates and turnover rates exceeding acceptable levels. These issues adversely affect the company's performance and productivity. Ineffective training and inconsistent career development are identified as primary factors contributing to job dissatisfaction and low employee retention. Therefore, this study aims to explore how employee development experiences, specifically through training and career development, influence employee retention. Job satisfaction is examined as a mediator in this relationship. The research adopts a quantitative approach with a causal/correlational research design. A sample of 60 employees participated in the study, providing data through questionnaires. The analysis utilizes path analysis with Smart-PLS 3.0 software, focusing on evaluating both the measurement model and structural model. The findings reveal that training significantly enhances employee retention but does not significantly affect job satisfaction. Conversely, career development does not directly impact employee retention but significantly influences job satisfaction. Job satisfaction is found to mediate the relationship between career development and employee retention but does not mediate the relationship between training and employee retention. These findings underscore the critical role of training and career development in improving staff retention at PT. Pegadaian Kanwil I Medan. The study highlights the importance of enhancing training programs and emphasizing career development to boost employee satisfaction and retention.